Analysis of the Padang City’s Labor Force with Least Square Method - mifttahul rezqy; Ade Salma Rahayu; Muhammad Rifqi Hananda; Muhammad Wahyu Alrasyid (Journal of Applied Mathematics and Modelling, 2025)
The labor force is an important indicator in the labor sector that reflects the number of working age people participating in economic activities, so its changes from year to year need to be analyzed quantitatively to support regional development planning. Padang City as the center of economic activity in West Sumatra Province shows relatively stable labor force development but still fluctuates, so a forecasting method is needed that is able to provide an accurate picture of the development of the labor force in the coming period. This study aims to forecast the number of Padang City workforce in 2026 using the Least Square method based on historical data for the 2017–2025 period. The Least Square method is used because it is able to form the best linear trend line with the principle of minimizing the number of squares of the error between the actual data and the value of the forecast result. The accuracy level of the forecast results was evaluated using Mean Absolute Percentage Error (MAPE). The results of the study show that the number of Padang City workforce in 2026 is projected to reach around 509,359 people with a MAPE value of 1.91%, which indicates that the Least Square method has an excellent level of forecasting accuracy and is suitable for use as a basis for data-based employment policy planning.